Analysis Of Liquidity Ratio And Solvability Ratio On The Financial Performance Of Sepakat Sejahtera Syariah Cooperative - Kartikaningrum, Sari (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
Abstract: The population of this research is the Sepakat Sejatela Syariah Cooperative from 2020 to 2022. The data collection method used is the library survey method. The data used in this research was obtained from the Indonesian Stock Exchange website (www.idx.co.id) and the Sepakat Sejahtera Syariah Cooperative website (https: //ntbmall.com) /store/. This data is secondary data in the form of the next report. Koperashi-Syariah-Prosperity Agreement). The data analysis technique used is to analyze data by describing or illustrating the data using liquidity ratios (current ratio, short-term ratio, liquidity ratio) and solvency ratios (debt to asset ratio, debt to asset ratio). Descriptive analysis whose aim is to analyze. Analysis of long-term equity and debt ratios). The results of the analysis are as follows. (1) Liquidity Ratio: Based on the average calculation for 2020-2022, the current ratio is 1224.67%, the quick ratio is 1221.07%, and the current ratio is less than 636.91%. Because this ratio is above the institutional average, it is recommended for institutions to maintain their financial performance and increase profits in the coming year. Businesses must manage the capital invested in assets, increase sales, and reduce operational costs incurred. Keywords: Liquidity, Solvency, Financial Performance